L’indemnisation du préjudice résultant de la perte de la capacité de gains - Crépeau, Paul-A. (Assurances)

(untitled) (HEC Montréal, 1987)
At the XIIth International Congress of Comparative Law which was held in Sydney, Australia last August, Pr Paul-A. Crépeau presented a General Report on the evaluation of damages for the loss of future earning capacity resulting from an accident. Prof. Crépeau is Wainwright Professor of Civil Law and Director of the Quebec Research Centre of Private and Comparative Law at McGill University. Extracts of this Report are here presented.